Levi Strauss & Co. : driving adoption of green chemistry - Strand, Robert; Mulvihill, Martin (London : SAGE Publications Ltd, 2017)
This case examines the challenges and opportunities faced by Levi Strauss & Co. (LS&Co.) as it attempts to help establish a cross-industry sustainability initiative to eliminate hazardous chemicals in the apparel supply chain. LS&Co.s Screened Chemistry Program screened chemical formulations against human and environmental health hazard endpoints before they chemicals entered the supply chain. This shift represents a radical departure from the status quo that requires widespread collaboration across the industry to implement. This case explores the associated challenges and opportunities to achieve cross-industry collaboration to achieve a sustainability objective.
Originally published: Strand, R., & Mulvihill, M. (2016). Levi Strauss & Co.: Driving adoption of green chemistry. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Levi Strauss and Company; Jeans (Clothing) -- United States; Clothing trade -- United States; Hazardous substances -- United States; Chemicals -- Safety measures -- United States; Green chemistry -- United States